QS5: Cryopreserved Adipose for Hypodermal Augmentation After Full-thickness Burns. (July 2021) - Loder, Shawn J.; Leftwich, Patricia A.; Chinnapaka, Somaiah; Nerone, Wayne V.; Lee, Phoebe L.; Marra, Kacey G.; Asim, Ejaz; Kokai, Lauren E.; Rubin, J. Peter
Abstract : Purpose: Burn and blast injuries to the face and extremities are highly morbid injuries affecting quality of life, ability to work, and psychosocial well-being. Without exception, extensive burn injuries require surgical debridement, with standard of care reconstruction involving autologous skin grafting to restore cutaneous integrity. This treatment modality is limited in extensive burns or in highly visible areas by lack of donor site and/or soft tissue deficits resulting in significant disfigurement. Hypodermal restoration via autologous adipose transplantation provides padding for the overlying skin, helps restore native features, and enhances contour and texture. However, this technique is limited by graft retention and often requires multiple rounds of grafting and consequently, multiple rounds of surgery, each with separate anesthesia, to achieve adequate results. The goal of this study was to demonstrate the therapeutic validity and efficacy of utilizing cryopreserved adipose to avoid multiple liposuction events when serial skin and fat grafting procedures are performed to restore epidermal, dermal, and hypodermal integrity after full-thickness burn. Methods: Adipose was collected from female Yorkshire swine and processed day-of-collection for immediate cryopreservation. This adipose was preserved for 3 months prior to initiation of the next stage of the experiment. After three-month elapse, female Yorkshire swine received 16, 4x4 cm full-thickness burns using an electric brand. After 48 hours, eschar was removed down to fascia. Skin grafts were collected as split-thickness skin grafts. The pigs were maintained for 8 weeks from time of engraftment and interval serum, photography, ultrasound, and biopsies were collected. At 8 weeks post-engraftment animals were sacrificed and all wounds were collected for histology and proteomic evaluation. Results: Split thickness skin graft take was greater than 95% in all injuries. Adipose grafts from Group B, were noted to remain present and incorporated into the granulation tissue in absence of skin graft with viability confirmed on biopsy. Initial increase in granulation layer thickness was noted in presence of fat graft with Group B vs. Group A. On serial ultrasound assessment, penetrating adipose grafts from Group D were noted to be present without gross resorption at all time points. Cryopreserved adipose remained viable throughout the duration of the experiment with histologic evidence of incorporation at 8 weeks post-operative. Conclusion: Burn and blast injuries predominantly affect military personnel and first responders for whom improvement in protective equipment has decreased mortality without resolving the risk of morbidity to the face or extremities. Hypodermal augmentation with lipografting as part of a strategy of autologous skin grafting addresses contour deficits and skin quality, however is limited by the need for multiple liposuction and grafting procedures, requiring multiple trips to the operating room with increased surgical and anesthetic risk and high economic burden. Here we demonstrate cryopreservation of adipose as an avenue to alleviate that burn.